Social and Psychological Experiences of Senior Citizens to Cope with Their Lives - Paudel, Kalpana (Janapriya Journal of Interdisciplinary Studies, 2019)
Aging is a normal, inevitable, biological and universal phenomenon and is the outcome of certain structural and physiological changes that take place in different parts of the body as the life years increases. During ageing process, coping with the situations of everyday life and meeting its demands become more difficult than before. This study mainly focused on the experiences of senior citizens to cope with their lives. A descriptive qualitative case study design was used to explore the experiences. Twenty-five senior citizens from Pokhara Aged Shelter were selected in the study. In-depth interview was used to collect primary data. Qualitative data was recorded; transcribed and thematic analysis was made. Elderly people express themselves as useless and worthless. They think that they have nothing to contribute to social life and the community. Social activities are reduced after ageing. They have fear of pain, disability, decline, loss of control and death and also have feelings of anxiety, fear and powerlessness. Elderly people have negative feelings such as emptiness, sadness, resignation, frustration, loneliness and regret because of being alone, limited activities or troubles to cope with ageing. They feel discouraged and helpless. During the ageing process, they give up daily activities gradually. Elderly people missed having somebody to share their small daily experiences. Family is an important factor that contributed to the elderly people’s ability to cope with. Hence, the issue of senior citizen and old age should be addressed appropriately as other social problems in society.